Agonistic Activation of Cytosolic DNA Sensing Receptors in Woodchuck Hepatocyte Cultures and Liver for Inducing Antiviral Effects - Suresh, Manasa; Li, Bin; Huang, Xu; Korolowicz, Kyle E.; Murreddu, Marta G.; Gudima, Severin O.; Menne, Stephan (Frontiers in Immunology, 2021)
Immune modulation for the treatment of chronic hepatitis B (CHB) has gained more traction in recent years, with an increasing number of compounds designed for targeting different host pattern recognition receptors (PRRs). These agonistic molecules activate the receptor signaling pathway and trigger an innate immune response that will eventually shape the adaptive immunity for control of chronic infection with hepatitis B virus (HBV). While definitive recognition of HBV nucleic acids by PRRs during viral infection still needs to be elucidated, several viral RNA sensing receptors, including toll-like receptors 7/8/9 and retinoic acid inducible gene-I-like receptors, are explored preclinically and clinically as possible anti-HBV targets. The antiviral potential of viral DNA sensing receptors is less investigated. In the present study, treatment of primary woodchuck hepatocytes generated from animals with CHB with HSV-60 or poly(dA:dT) agonists resulted in increased expression of interferon-gamma inducible protein 16 (IFI16) or Z-DNA-binding protein 1 (ZBP1/DAI) and absent in melanoma 2 (AIM2) receptors and their respective adaptor molecules and effector cytokines. Cytosolic DNA sensing receptor pathway activation correlated with a decline in woodchuck hepatitis virus (WHV) replication and secretion in these cells. Combination treatment with HSV-60 and poly(dA:dT) achieved a superior antiviral effect over monotreatment with either agonist that was associated with an increased expression of effector cytokines. The antiviral effect, however, could not be enhanced further by providing additional type-I interferons (IFNs) exogenously, indicating a saturated level of effector cytokines produced by these receptors following agonism. In WHV-uninfected woodchucks, a single poly(dA:dT) dose administered via liver-targeted delivery was well-tolerated and induced the intrahepatic expression of ZBP1/DAI and AIM2 receptors and their effector cytokines, IFN-b and interleukins 1b and 18. Receptor agonism also resulted in increased IFN-g secretion of peripheral blood cells. Altogether, the effect on WHV replication and secretion following in vitro activation of IFI16, ZBP1/DAI, and AIM2 receptor pathways suggested an antiviral benefit of targeting more than one cytosolic DNA receptor. In addition, the in vivo activation of ZBP1/DAI and AIM2 receptor pathways in liver indicated the feasibility of the agonist delivery approach for future evaluation of therapeutic efficacy against HBV in woodchucks with CHB.